THE TRADITION OF PESANTREN AS A CULTURE IN THE FORMING OF SANTRI PERSONALITY (STUDY at NANGGROE ACEH DARUSSALAM) - Abd Aziz Hsb; Darwyan Syah; Sri Rahmi (STIT AL-AMIN KREO TANGERANG, 2020)
This study aims to describe and analyze the pesantren tradition that has become a culture in the effort to form the personality of the students in the pesantren in accordance with the teachings of Islam. For that research using quantitative analysis through descriptive and inferential analysis. The research was conducted in 3 (three) Islamic boarding schools in the area, namely the Dayah Modern aarul Ulum Islamic Boarding School, the Dayah Darul Ihsan Abu Hasan Kruengkale Islamic Boarding School in Aceh Besar, the Dayah Darul Maghhfiroh Islamic Boarding School, with a sample of 250 people from the total population. Data were collected using an instrument questionnaire as a data collection tool. From the results of the study, it was found that there was no significant difference between the pesantren traditions as seen in the gender of the santri, as well as the pesantren tradition as measured by age demographics which showed no difference in the perceptions or views of the santri towards the pesantren tradition. In the student personality variable from the research results, it was found that there was no difference in perceptions of the personality of the students through gender demographics, a different thing was seen in the perceptions of the students on the personality of the students as seen in the age demographics which showed differences in the personality of the students based on age. In addition, there is a significant influence on the Islamic boarding school tradition through the dimensions of rihlah ilmiyah, the tradition of reading the yellow book, the Arabic language tradition, the tradition of practicing Tariqat, and the tradition of memorizing on the formation of the personality of the students. It was also found that the dominant factors affecting the personality of the students were the tradition of practicing the Tariqat and the tradition of rihlah ilmiyah. Thus it can be concluded that the formation of the personality of students in the santri is very closely related to the existence of a culture that has been formed from the traditions that exist in the pesantren environment, from this study it is hoped that it will provide input to the leadership and related parties to be used as a benchmark or material in policy making so as to be able to provide changes to the attainment of a quality student personality